2017
DOI: 10.1097/ta.0000000000001379
|View full text |Cite
|
Sign up to set email alerts
|

Tissue injury suppresses fibrinolysis after hemorrhagic shock in nonhuman primates (rhesus macaque)

Abstract: BACKGROUND Hypoperfusion is associated with hyperfibrinolysis and early death from exsanguination, whereas tissue trauma is associated with hypofibrinolysis and delayed death from organ failure. We sought to elucidate the effects of injury patterns on fibrinolysis phenotypes using a nonhuman primate (NHP) model. METHODS NHPs were randomized to three injury groups (n = 8/group): 60 minutes severe pressure-targeted controlled hemorrhagic shock (HS); HS + soft tissue injury (HS+); or HS + soft tissue injury + f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Furthermore, the duration that a patients remains in a hypercoagulable state, the higher risk of mortality (23). Animal work has demonstrated that tissue injury causes fibrinolysis shutdown, while hemorrhagic shock increases fibrinolysis(12, 24). These early changes in may represent a response to injury in attempt to attain hemostasis but retain blood flow to organs, but prolongation of deranged coagulation may be pathologic.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the duration that a patients remains in a hypercoagulable state, the higher risk of mortality (23). Animal work has demonstrated that tissue injury causes fibrinolysis shutdown, while hemorrhagic shock increases fibrinolysis(12, 24). These early changes in may represent a response to injury in attempt to attain hemostasis but retain blood flow to organs, but prolongation of deranged coagulation may be pathologic.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps gene modification of the coagulation proteins may provide an opportunity in the future. Nonhuman primates represent the best approximation at this time , but are logistically prohibitive [18, 19]. Although rats are widely used in coagulation studies, they represent a limited animal model to study TIC [5].…”
Section: Discussionmentioning
confidence: 99%
“…In primary coagulopathy, trauma and traumatic shock give rise to systemic and persistent thrombin generation associated with platelet dysfunction from the early to late phases of trauma. Fibrinolytic systems bring about dynamic two‐phase changes: increased fibrinolysis due to shock‐induced t‐PA release at an early stage, and the inhibition of fibrinolysis due to persistent expression of PAI‐1 at a later stage of trauma . These imbalances are predictors of mortality in observational studies, and importantly, those patients with physiologic levels of fibrinolysis on admission have been shown to have the lowest mortality .…”
Section: Proposed Stratification Of Tic Clinical Presentation For Invmentioning
confidence: 99%
“…Fibrinolytic systems bring about dynamic two-phase changes: increased fibrinolysis due to shock-induced t-PA release at an early stage, 50,70 and the inhibition of fibrinolysis due to persistent expression of PAI-1 at a later stage of trauma. 51,71,72 These imbalances are predictors of mortality in observational studies, and importantly, those patients with physiologic levels of fibrinolysis on admission have been shown to have the lowest mortality. [8][9][10][11] However, depending on the mechanism of injury, and the type and speed of resuscitative measures imparted, the evolution from hyperfibrinolytic-type to hypofibrinolytic-type can occur in minutes to hours.…”
Section: Enhanced Versus Inhibited Fibrinolysismentioning
confidence: 99%